2017
DOI: 10.1039/c7fo01075c
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofin vitrodigestion phases on the stability and bioaccessibility of carotenoids and their esters in mandarin pulps

Abstract: The composition of carotenoids (carotenes and free and acylated xanthophylls) and their bioaccessibilities were determined for the first time in pulps of mandarins cultivated in Brazil. Two cultivars of mandarin, Citrus reticulata Blanco cv. 'Ponkan' and Citrus reticulata × C. sinensis cv. 'Murcott', showed higher contents of most carotenoids compared to those found in C. deliciosa Tenore cv. 'Rio'. The major carotenoids in mandarin cv. 'Ponkan' and 'Murcott' were (all-E)-β-cryptoxanthin laurate (19-21%), (all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 61 publications
5
29
0
Order By: Relevance
“…Some studies using this new standardized methodology have already surfaced . However, because this model has not been designed to specifically digest carotenoid‐rich foods, we consider that further advanced adjustments are required to improve the base model proposed by Minekus et al .…”
Section: In Vitro Digestion Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies using this new standardized methodology have already surfaced . However, because this model has not been designed to specifically digest carotenoid‐rich foods, we consider that further advanced adjustments are required to improve the base model proposed by Minekus et al .…”
Section: In Vitro Digestion Modelsmentioning
confidence: 99%
“…Therefore, in vitro digestion models allow study of the degradation of carotenoids during the different phases of digestion. During recent years, several studies have reported losses in the range of 20–30% of the initially fed carotenoid doses during the in vitro digestion . Blanquet‐Diot et al .…”
Section: Factors Affecting Carotenoid Bioaccessibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The encapsulation of carotenoids inside oil droplets can be compared to their incorporation into the mixed micelles formed during intestinal digestion. Many reports shows greater micellarization of xanthophylls than carotenes in vegetables due to their degree of polarity (Petry and Mercadante, 2017;Dube et al 2018). Also, β-carotene, lycopene, α-carotene and lutein micellarization are affected differently by addition of unsaturated fat (higher micellarization) or saturated fat (lower micellarization) (Mashurabad et al 2017).…”
Section: Tracking the Carotenoid Over The Microemulsion Productionmentioning
confidence: 99%